Analisis Risiko Kejadian Obesitas pada Ibu Rumah Tangga di Desa Gemba, Kairatu Kabupaten Seram Bagian Barat - Mulyadi Muyadi; Maryam Lihi; Abubakar Lating (HIGIENE: Jurnal Kesehatan Lingkungan, 2015)
Nutritional problems are problems that exist in each country either underweight or overweight. This study aims to determine the risk factors affecting the incidence of obesity among housewives. Respondents measured height, weight, LILA, and WHR, so it can be seen that the respondentsin the category of overweight, obese I,II or III. This research is quantitative case control design. Thisstudy was carried out from September to October in Gemba Village Kairatu District Seram West Section in 2012. The samples in this study were housewives who are obese and non-obese housewives asa controls. The result showed that there was no significant association between dietary risk factorswith the incidence of obesity in the mother’s household, where (p=0.221, OR=1.654). There is no significant relationship between physical activity risk factors with the incidence of obesity in the motherhouseholds (p=1.000, OR=1.000). There is significant association between family history with the incidence of obesity in the mother households (p=0.049, OR=0.375). there is a significant relationshipbetween family environment risk factors with incidence of obesity in the mother households(p=0.078, OR=0.351).Keyword : Obesity, Factor Risk, Housewife